Measuring Similarity Between Dynamic Ensembles of Biomolecules - Yang, Shan (2014)
Methods for comparing ensembles of biomolecules assess the population overlap between distributions but fail to fully quantify structural similarity. We present a simple and general approach for quantifying population overlap and structural similarity between ensembles. This approach captures improvements in the quality of ensembles determined using increasing input experimental data that go undetected using conventional methods and reveals unexpected similarities between RNA ensembles determined using NMR and molecular dynamics simulations.